Revealing the Inhibitory Effect of Ginseng on Mitochondrial Respiration through Synaptosomal Proteomics. Issue 11 (15th May 2018) - Kong, Dezhi; Tian, Xiaolin; Li, Yunshan; Zhang, Saihang; Cheng, Yiru; Huo, Lifang; Ma, Huanhuan; Yang, Zuxiao; Ren, Leiming; Zhang, Mingquan; Zhang, Wei
Abstract: Ginseng, the active ingredients of which are ginsenosides, is the most popular herbal medicine and has potential merit in the treatment of cerebral disorders. To better understand the function of Ginseng in the cerebral system, we examined changes in the protein expression profiles of synaptosomes extracted from the cerebral cortical and hippocampal tissues of rats administered a high or low dose of Ginseng for 2 weeks. More than 5000 proteins belonging to synaptosomes were simultaneously identified and quantitated by an approach combining tandem mass tags with 2D liquid chromatography‐mass spectrometry (LC‐MS). Regarding differentially expressed proteins, downregulated proteins were much more highly induced than upregulators in the cerebral cortical and hippocampal synaptosomes, regardless of the dose of Ginseng. Bioinformatic analysis indicated the majority of the altered proteins to be located in the mitochondria, directly or indirectly affecting mitochondrial oxidative respiration. Further functional experiments using the substrate‐uncoupler inhibitor titration approach confirmed that three representative ginsenosides were able to inhibit oxidative phosphorylation in mitochondria. Our results demonstrate that Ginseng can regulate the function of mitochondria and alter the energy metabolism of cells, which may be useful for the treatment of central nervous disorders.